The flux pinning properties of yttrium substitution in Bi-2223 superconductor / Siti Sarah Nordin - Nordin, Siti Sarah (Faculty of Applied Sciences, 2017)
This report present the study of flux pinning properties as well as the superconducting properties of Bi1.6-xYxPb0.4Sr2Ca2Cu3O superconductor. The samples with varying value of Y (x =0.00, 0.02, 0.05, 0.10 and 0.20) were prepared by using solid state method. The samples were characterized by using four point probe and X-ray diffraction (XRD). The critical temperature, Tc and critical current density, Je measurement were done using four point probe method without applied magnetic field. Pure sample (x = 0.00) was observed to have the highest value of Tc and Jc. The Tc (onset) and Tc (zero) for pure sample are 111 K and 97 K respectively. The Jc value for pure sample is 1.590 A/cm2 at temperature 40 K. The flux pinning properties were observed using four point probe method with applied magnetic field varying from O.OOT to 0.33T. The Jc-B characteristic show that pure sample has better flux pinning properties compared to other samples and has the better peak position of Fp/Fpmax in the magnetic field. The XRD pattern shows that all samples exhibit orthorhombic structure and peak at 20 = 26° is being diminished at x = 0.10 and 0.20. From the results, it is show that yttrium substituted samples reduced the superconducting properties and as well as the flux pinning properties of the Bi2223 superconductor.